Microwave Ablation of T1a and T1b Renal Masses: A Retrospective Study - Assim Saad Eddin; Karan Rao; Bradford Oliva; Ajmain Chowdhury; Shetty Zubin; Chad Tracy; Brian J. Smith; Sandeep T. Laroia (Journal of Clinical Interventional Radiology ISVIR)
The aim of this study was to evaluate the efficacy and safety of microwave ablation (MWA) for the treatment of T1a and T1b renal masses, with size ranges between 1.2 and 6.5 cm. A retrospective review was performed at a single tertiary comprehensive cancer center between June 2019 and June 2023 of 49 consecutive patients (53 total procedures) who underwent MWA for renal masses. The Solero microwave tissue ablation system (Angiodynamics, Latham, NY, United States) was utilized. Patient demographics, renal mass characteristics, and procedural outcomes were collected. Serum creatinine and estimated glomerular filtration rate (eGFR) were utilized to assess renal functional outcomes. Oncologic outcomes were assessed using evidence of local tumor recurrence on contrast-enhanced cross-sectional imaging, local recurrence-free probability at 1 and 2 years, and overall survival (OS) using the Kaplan–Meier analysis.Forty-nine patients (57% males and 43% females) with a median age of 72 years (range, 38–84 years) underwent 53 MWA procedures. The mean renal mass size was 2.8 ± 0.94 cm (range, 1.2–6.5 cm). Most of the renal tumors were T1a. Three of the 53 total renal tumors were larger than 4 cm (T1b) and the remaining 50 were less than 4 cm in size (T1a). The largest tumor that was ablated was 6.5 cm in size. All the patients were placed under general anesthesia (intubated) before the MWA procedure. A median microwave energy of 100 W (range, 60–140 W) was used. The mean duration of the MWA was 3.9 ± 1.5 minutes, with a 100% technical success rate. Four patients (8.2%) experienced complications, two (4.1%) of whom experienced a major complication. There was no clinically significant change in renal function from pre- to postablation on day 1 or at 3 months. Furthermore, local tumor recurrence was observed in three (6.1%) patients at 2.5, 15, and 25 months postablation. Local recurrence-free probability was 98 and 93% at 1 and 2 years, respectively. The OS was 98 and 87% at 1 and 2 years, respectively. MWA continues to prove to be an effective technique that can be used to treat small renal masses including oncocytomas, with high technical success, low complication rate, low risk of adverse renal functional outcomes, and encouraging results for sustained tumor control.